Economic Analysis of Law: Some Realism About Nominalism - Leff, Arthur A. (1974)
With the publication of Richard A. Posner's Economic Analysisof Law, that field of learning known as Law and Economics has reached a stage of extended explicitness that requires and permits extendedand explicit comment